MODEL TRIANGULASI DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Afriani, Raden Irna; Handayani, Novi; Apriani, Tri; Husni, M. (LPPM Universitas Bina Bangsa, 2023)
Financial statement fraud is an act, deed or crime committed intentionally by certain parties that can cause misstatement of information whose value is material in the financial statements. Fraud is one type of fraud that often occurs in financial statements. This study aims to analyze financial statement fraud with one type of fraud, namely the triangulation model which consists of three factors, namely pressure, opportunity, and rationalization. The method used in this research is a quantitative approach. The population used in this study is the consumer goods sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2021 period as many as 75 companies. The sample in this study were 94 companies which were selected using the Purposive Sampling Technique. The method used in this research is the documentation and analysis of multiple linear regression data. The results showed that the partial hypothesis test was the significance value (Sig) of (0.865 > 0.05) for the Pressure variable (X1), while the significance value (Sig) of (0.032 < 0.05) was in the Opportunity variable (X2). , and a significance value (Sig) of (0.114 > 0.05) on the Rationalization variable (X3). The conclusion of this study is that partial pressure has no effect on financial statement fraud, opportunity has no effect on financial statement fraud, and rationalization has no effect on financial statement fraud.